2018
DOI: 10.3329/bjp.v13i1.34117
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective potential and chemical characterization of Artocarpus lakoocha fruit extract

Abstract: <p class="Abstract">Artocarpus lakoocha fruits are widely consumed as food. The study was aimed at evaluating its hepatoprotective activity and chemical constituents. The extract was analysed by HPLC for the presence of flavonoids and phenolic compounds. Hepatoprotective potential was determined in mice following 8 days of extract or silymarin (standard therapy) administration. Hepatotoxicity was induced by administration of paracetamol (500 mg/kg). The blood and liver of treated and untreated mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…Liver is the major organ which plays a key roles in processing of critical biochemical and physiological phenomena including metabolism and detoxification of endogen and exogenous compounds, such as drugs and xenobiotics, homeostasis, growth, energy and nutrient supply [1,2]. Hepatic injury could be occurred by hepatotoxic agents including drugs, alcohol and viral infections [3]. Liver diseases like jaundice, cirrhosis and fatty liver have been public health concern across the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liver is the major organ which plays a key roles in processing of critical biochemical and physiological phenomena including metabolism and detoxification of endogen and exogenous compounds, such as drugs and xenobiotics, homeostasis, growth, energy and nutrient supply [1,2]. Hepatic injury could be occurred by hepatotoxic agents including drugs, alcohol and viral infections [3]. Liver diseases like jaundice, cirrhosis and fatty liver have been public health concern across the world.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover they can have serious side effects [5]. Due to the fact, a huge number of medicinal plants have been trialed to figure out regenerative and hepatoprotective activity [3]. Approximately 160 phytochemical constituents originated from 101 plants have been reported to be potentially hepatoprotective [6].…”
Section: Introductionmentioning
confidence: 99%
“…Liver is the major organ which plays a key roles in processing critical biochemical and physiological phenomena including metabolism and Detoxification of endogen and exogenous compounds, such as drugs and xenobiotics, homeostasis, growth, energy and nutrient supply [1,2 ] Hepatic injury could be occurred by hepatotoxic agents including drugs , alcohol and viral infections. [ 1,3 ]Liver diseases like jaundice, cirrhosis and fatty liver have been public health concern across the world. Prevalence of chronic liver disease worldwide is 18 Deoxy-niazimicine [ 10,11,12] A great number of pharmacological activity has also been reported .Aqueous and alcoholic extracts of leaves and roots of Moringa oleifera has been reported to have a strong in-vitro anti-oxidant and radical scavenging activity [12] while Methanolic and ethanolic extract of leaves against pentylenetetrazole and maximal electroshock induced convulsions, demontrated significant anti-convulsant activity [13,14] Potent antidiabetic activity from different extracts of leaves , seed and pod, has also been reported [ ,15,16, 17] an investigation against seed power also revealed its Anti-asthmatic activity [ 19,18] Study on Ethanolic extracts of Moringa oleifera exhibited potent anti-tumor [ 19] and Anthelmintic activity [21 , 22] Another study of alcoholic extracts of leaves as well as seeds has showed effectiveness on isoniazid, rifampicin, and pyrizinamide induced liver damage.…”
Section: Introductionmentioning
confidence: 99%
“…and the extracts were given orally using oral gavage. Since most studies used 100-500 mg extract per kg of body weight [22][23][24], the dose of 250 mg/kg was, therefore, selected for this study. The body weights (in grams) of the rats were recorded biweekly for six weeks of the experiment.…”
Section: (D) Induction Of Fibrosismentioning
confidence: 99%